Swelling, Thermal, and Hydraulic Properties of a Bentonite-Sand Barrier in a Deep Geological Repository for Radioactive Wastes: Effect of Groundwater Chemistry, Temperature and Physical Factors - Alzamel, Mohammed (Université d'Ottawa / University of Ottawa, 2022)
Electricity generation at nuclear power plants produces a large amount of high-level radioactive waste (HLW) every year, which has long-term detrimental effects on humans and the environment. Other applications of nuclear technology (e.g., medicine, research, nuclear weapons, industry) also produce radioactive waste (e.g., low-level radioactive waste, LLW, Intermediate-level waste, ILW). The potential of deep geological repositories (DGRs) as an option for disposal of radioactive waste (HLW, ILW, LLW) has been examined in several countries, including Bulgaria, Canada, China, Finland, France, Germany, India, Japan, Russia, Spain, Sweden, Switzerland, Ukraine and the United Kingdom and are still under discussion. In Ontario, Canada, DGRs with a multi-barrier system comprised of a sedimentary rock formation (i.e., a natural barrier) and an engineered barrier system (EBS) are currently under consideration. An EBS consists of various components, such as waste containers, buffer, backfill, and tunnel sealing materials, intended to prevent the release of radionuclides. Several engineered barrier materials, including a mixture of bentonite and sand, are currently being considered for use in DGRs for nuclear waste in Ontario. Bentonite has some advantageous physical and chemical properties, such as low permeability, high plasticity, and high swelling potential, which provide it with a good sealing ability and thus make it an effective barrier. However, interaction between the compacted bentonite–sand mixture and underground water chemistry fluids (chemical factor) in the DGR could significantly alter the favourable properties of bentonite (e.g., swelling potential), thus influencing its performance when used in an EBS and eventually jeopardizing the overall safety of DGRs. In addition, other parameters, such as the clay content, initial dry density and moisture content of the compacted barrier (physical factors), as well as the presence of salts in groundwater may affect the physical and physiochemical properties of barrier materials. Moreover, during the lifetime of a DGR for used spent fuel, the bentonite–based barrier material will not only be exposed to a broad range of groundwaters with different chemical compositions, but also to high temperatures (heat generated by the nuclear wastes) (thermal factor). Thus, the interaction between the compacted bentonite–sand mixture, the surrounding groundwater and the heat from the nuclear waste material could jeopardize the favourable properties of the bentonite-based (bentonite-sand) barrier material. Properties of a bentonite-sand barrier is an important characteristic to study while designing and constructing an EBS for a DGR. Thus, to understand and assess the operations of DGRs in Ontario, comprehensive studies must be performed on engineering properties like swelling behaviour, permeability, and thermal conductivity. The goal of this research study is to experimentally investigate the physical, chemical and thermal factors that influencing the engineering properties of a barrier material made up of bentonite-sand composite used in DGRs for nuclear waste in Ontario. Compacted samples are subjected to one-dimensional free swell test to understand the swelling behaviour of the material. Hydraulic conductivity was investigated using a flexible wall permeability test. Thermal conductivity and diffusivity were tested using Decangon KD2 Pro with TR-1 and and KS-1 sensors. The specimens contain different bentonite–sand mixture ratios (20:80, 30:70, 50:50, and 70:30 dry mass), and they are tested under conditions with differing bentonite content, dry density, groundwater chemistry, and temperature. Additional tests were conducted to investigate the microstructure of the specimens. These tests include X-ray diffraction (XRD) analysis, mercury intrusion porosimetry (MIP), and thermogravimetric analyses (TG/DTG). The results reveal that the time and strain required to achieve maximum swelling of compacted bentonite–sand specimens increase with the increase of initial dry density. The simulated saline solutions of Guelph and Trenton groundwater are found to suppress the swelling of the bentonite–sand specimens. This in turn leads to the increase of hydraulic conductivity and decrease of thermal properties of the barrier material. However, the impact of the salinity is significantly reduced by increasing the dry densities and sand content of the compacted material. Moreover, the coupled effect of salinity and temperature decreases the swelling potential of the bentonite-sand mixture. Also, some transformation of Na-montmorillonite into Ca-Montmorillonite was observed. The results also indicate that some montmorillonites might have been transformed into illites, thereby further decreasing the swelling potential of the bentonite-based barrier.
Keywords: Bentonite-sand mixture; Engineered barrier material; Deep geological repository; hydraulic conductivity; pore water chemistry; thermal conductivity; temperature; nuclear waste management; swelling